9 Dual antiplatelet therapy to inhibit myocardial injury in patients with high-risk coronary artery plaque: a randomised controlled trial. (15th May 2019) - Moss, Alastair J; Dweck, Marc R; Doris, Mhairi K; Andrews, Jack PM; Bing, Rong; Forsythe, Rachael O; Cartlidge, Timothy R; Pawade, Tania A; Daghem, Marwa; Raftis, Jennifer B; Williams, Michelle C; Beek, Edwin JR van; et al.
Abstract : Introduction: High-risk coronary atherosclerotic plaque is associated with higher plasma troponin concentrations suggesting ongoing myocardial injury that may be a target for dual antiplatelet therapy. The aim of this study is to determine whether ticagrelor reduces high-sensitivity troponin I concentrations in patients with established coronary artery disease and high-risk coronary plaque using coronary 18F-fluoride positron emission tomography-computed tomography. Methods: In a randomised double-blind placebo-controlled trial, patients with multivessel coronary artery disease underwent coronary 18F-fluoride positron emission tomography-computed tomography and measurement of high-sensitivity cardiac troponin I and were randomised (1:1) to ticagrelor 90 mg twice daily or matched placebo. The primary endpoint was troponin I concentration at 30 days in patients with increased coronary 18F-fluoride uptake. Results: In total, 202 patients were randomized and 191 met the pre-specified criteria for inclusion in the primary analysis. In patients with increased coronary 18F-fluoride uptake (n=120/191) there was no evidence that ticagrelor had an effect on plasma troponin concentrations at 30 days (ratio of geometric means for ticagrelor versus placebo, 1.11, [95% confidence interval 0.90 to 1.36], p=0.32). Over 1 year, ticagrelor had no effect on troponin concentrations in patients with increased coronary 18F-fluoride uptake (ratio of geometric means, 0.86, 95% confidence interval 0.63 to 1.17, p=0.33). Conclusion: Dual antiplatelet therapy with ticagrelor does not reduce plasma troponin concentrations in patients with coronary 18F-fluoride uptake. This suggests that subclinical plaque thrombosis does not contribute to ongoing myocardial injury in this setting.